Use of XANES and XPS to investigate the effects of ethanol contamination on anti-wear ZDDP tribofilms. (July 2021) - Costa, H.L.; Evangelista, K.S.; Cousseau, T.; Acero, J.S.R.; Kessler, F.
Abstract: This work uses synchrotron radiation XANES and XPS measurements to investigate the structure of ZDDP tribofilms formed from lubricants contaminated with anhydrous and hydrated ethanol (5%wt). The tribofilms were formed at 40 °C from PAO8 lubricant containing only ZDDP additive onto carbon steel specimens using sliding tests, cylinder-on-flat configuration (line contact) under boundary lubrication. Ethanol increased friction as well as surface damage, detected by an increase in relative porous area. Angle-resolved measurements (15°, 45°, 90°) helped detecting differences along the thickness of the tribofilm. The amount of long-chain phosphates apparently reduced with ethanol, leading to reduced wear performance. The sulphides in the tribofilms were richer in Fe in the presence of ethanol, also indicative of more severe wear. Highlights: Effect of ethanol and water on ZDDP tribofilm formation was analyzed. Contaminated lubricants showed higher and more unstable friction coefficient. Ethanol and water in the lubricant increased surface damage. Ethanol contamination increased Fe in the sulfides present in the tribofilm. Phosphates chains in the tribofilm were shorter for contaminated lubricants.